Ferritin and Encapsulin Nanoparticles as Effective Vaccine Delivery Systems: Boosting the Immunogenicity of the African Swine Fever Virus C129R Protein - Yue Zhang; Yi Ru; Longhe Zhao; Rongzeng Hao; Yang Yang; Yajun Li; Rong Zhang; Chenghui Jiang; Haixue Zheng (Viruses)
Vaccination remains the most effective strategy for preventing infectious diseases. Subunit vaccines, which consist of antigenic components derived from pathogens, offer significant advantages in terms of biosafety, ease of preparation, and scalability. However, subunit vaccines often exhibit lower immunogenicity than whole-pathogen vaccines do. To address this limitation, coupling antigens with nanoparticles has emerged as a promising strategy for enhancing immune responses by mimicking pathogen structures and improving antigen presentation. This study evaluated the stability of ferritin (F-nps) and encapsulin (E-nps) nanoparticles and their efficient uptake by bone-marrow-derived dendritic cells (BMDCs) in vitro. In vivo studies demonstrated their effective targeting of lymph nodes. The African swine fever virus C129R protein was conjugated to ferritin and encapsulin nanoparticles to assess its ability to enhance antigen-specific immune responses. In murine models, both F-nps and E-nps significantly increased the immunogenicity of the C129R antigen, highlighting their potential as effective vaccine delivery systems. These findings underscore the promise of ferritin and encapsulin nanoparticles as delivery platforms for enhancing antigen immunogenicity and pave the way for the development of nanoparticle-based vaccines.